Size determination of mixed liquid and frozen water droplets using interferometric out-of-focus imaging. (July 2016) - Jacquot Kielar, Justin; Wu, Yingchun; Coëtmellec, Sébastien; Lebrun, Denis; Gréhan, Gérard; Brunel, Marc
Abstract: We record simultaneously interferometric out-of-focus images and digital in-line holograms of liquid and frozen water droplets. We show that the analysis of speckle-like out-of-focus images allows a quantitative estimation of the size of the particles which is corroborated by numerical reconstruction of holograms recorded simultaneously. Interferometric out-of-focus imaging could be extended to the characterization of ice in clouds in the atmosphere. Highlights: Interferometric out-of-focus imaging is used to measure size of liquid and frozen water droplets. Results are validated using digital in-line holography. Rate of errors is evaluated.